The multimedia communication model enhances public awareness of sustainable development and climate change adaptation in the Mekong Delta - Hieu, Ngo Thi Minh; Pham, Hang Thu (Edelweiss Applied Science and Technology, 2025)
As the Mekong Delta faces increasingly severe impacts from climate change, communication has become an essential tool for enhancing public awareness and promoting adaptive behaviors. However, most current campaigns remain overly generic, lacking in localized depth and failing to harness the full potential of multimedia communication to engage collective memory, cultural symbolism, and emotional resonance. This study assesses the effectiveness of a multimedia communication model in raising awareness of sustainable development and encouraging climate-adaptive actions among residents in five key provinces of the Mekong Delta: Cần Thơ, Vĩnh Long, Tiền Giang, Hậu Giang, and Trà Vinh. Employing a mixed-methods approach, the research combines quantitative surveys of 500 participants with in-depth qualitative interviews of 25 key informants and interpretive analysis of communication content. The findings reveal that over 70% of participants expressed an intention to take positive action after exposure to the multimedia messages, while approximately 60% reported concrete behavioral changes. Localized content—utilizing familiar imagery, regional dialects, and culturally embedded symbols—demonstrated significantly higher impact than standardized formats. Crucially, multimedia communication not only enhanced cognitive awareness but also activated environmental memory, fostered a sense of responsibility, and reinforced ecological moral norms. Based on these insights, the study advocates for the implementation of multimedia communication as a community-based intervention strategy. The model should integrate localized content, generational targeting, and collaboration with grassroots organizations to transform perception into sustainable behavioral change.